Testing the Mediating Role of Career Development in Affecting Intellectual Capital and Organizational Culture on Employee Performance: Evidence of Local Banks in Yogyakarta, Indonesia - Titi Laras; Rutha Mathilde Santana; Bambang Jatmiko; Tiyas Puji Utami (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to examine the role of career development in mediating the relationship between intellectual capital and organizational culture on employee performance.Design/Methodology/Approach: This study used a proportional stratified random sampling method with 126 permanent employees of local banks in Yogyakarta, Indonesia, as research respondents. The respondents included Head Office, Main Branch Office, and Senopati Branch Office. The data were collected by distributing a questionnaire, and the secondary data were in the form of data or documents that supported and strengthened the primary information from books, magazines, journals, and other documents. Then, the analytical tool utilized in this study was SEM (Structural Equation Modeling) to test the research hypotheses.Research findings: The results showed that intellectual capital and organizational culture had a positive and significant effect on career development and performance, but career development had no positive and significant effect on performance. Meanwhile, career development could not mediate the effect of intellectual capital and organizational culture on performance.Theoretical contribution/Originality: The study results contribute to the literature (body of knowledge), especially as additional discussion toward theory and literature related to intellectual capital, organizational culture, career development, and performance in local banks, which is still very limited.